UTILIZING SNOWBALL THROWING LEARNING MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES FOR SUB THEME AKU CINTA MEMBACA IN CLASS 4A SDN CUKIR 1 - Yasinta Nurlaila Diniyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to describe the improvement of students’ learning outcomes through the implementation of Snowball Throwing learning models for sub-themes “Aku Cinta Membaca” in class 4A SDN Cukir 1. This study utilized Classroom Action Research (CAR) which included several stages such as planning, action, observation and reflection. Data were obtained from test results, observations, documentation, and interviews. The results indicated that students’ learning outcomes increased from pre-cycle, cycle 1, and cycle II through the implementation of Snowball Throwing learning model. The percentage of students’ learning completeness in pre cycle was 21%; it was increased in cycle 1 by 60% and in cycle II with a high criterion, which was equal to 100%. The increase was also seen in the average score of the students. In pre-cycle, the average score was 6.73 while in cycle 1, it became 7.32 and increased in cycle II to 8.87. The result of this study concluded that the implementation of Snowbal Throwing learning model generated a more effective learning as well as improved students’ learning aoutcomes.